Enzymatic conversion of cassava starch to flour - Kong, Zi Ling (2015)
Cassava (Manihot esculenta Crantz) plays important role as the food source rich with carbohydrate content consumed by human in the world. It is the fourth vital basis of food after the rice, wheat and maize. Cassava starch has been widely used in industrial field including food processing, paper, wood, textile, pharmaceutical and chemical processing. This work aims to produce flour from cassava starch using microbial fungi. The pectinase enzyme derived from Aspergillus niger is used in the starch extraction due to its ability to enhance the starch yield without compromise the physical properties of the starch. At first, sample preparation from peeling, washing, drying to grinding was carried out using traditionally method. A. niger was cultured for 3 days to produce pectinase as a crude enzyme extract. Then, pectinase precipitate was fermented with cassava solution at different duration (3, 5, 7, 9 hrs) and temperature (30, 40, 50, 60°C) to obtain the optimum condition for cassava starch to reach its maximum extractability. Once the optimum condition was obtained, the starch recovery of cassava flour with pectinase enzyme treatment was evaluated. The nutrition analysis (i.e., moisture, ash, crude fat, crude fiber and protein content) of cassava starch was performed using standard American Association of Cereal Chemists (AACC) and Lowry method. The finding showed that the temperature range of 45-50°C and the duration of 6-7 hrs is the optimum condition for the, cassava starch extraction. The cassava flour with and without pectinase enzyme contain 10-12% of moisture, 1-3% of ash, 14% of fat, 1-3.5% of crude fiber and 191-364 ug/ml of protein. Besides that, this work also indicated that the pectinase enzyme treatment from A. niger had increased about 9% of the starch recovery of cassava flour.